Description of the last stadium larva of Erythrodiplax abjecta (Anisoptera: Libellulidae) from the eastern Colombian Andes - Palacino-Rodríguez, Fredy; Rache-Rodríguez, Leonardo Dionel; Castillo, Daniel R. (Zootaxa, 2019)
The final stadium larva of Erythrodiplax abjecta (Rambur) is described and illustrated based on reared and field collected specimens from Colombia.